Effects of Agricultural Expansion on Soil Carbon and Nitrogen Stocks in the Amazon Deforestation Arc - Azevedo, Jorge Cardoso de; Cardoso, Abmael da Silva [UNESP]; Lage Filho, Nauara Moura; Faturi, Cristian; Silva, Thiago Carvalho da; Domingues, Felipe Nogueira; Costa, Vladimir Eliodoro [UNESP]; Ruggieri, Ana Cláudia [UNESP]; Reis, Ricardo Andrade [UNESP]; do Rêgo, Aníbal Coutinho (MDPI, 2024)
Typical successions in land use affect the dynamics of carbon (C) and nitrogen (N) in the soil. This study aimed to determine the effects of land use change on soil organic carbon and N content and stocks in pastures, crops, and forests in the Amazon. Soil C and N stocks were assessed at depths of 30 and 100 cm to determine 13C isotopic abundance. The concentrations of C and N in crops were lower (p < 0.05) than those in other land use types. Soil organic C and soil N stocks for pasture (67.6, 144.8, 5.7, and 13.3) and forest (77.1, 137.5, 6.3, and 13.8) systems were similar, but greater than those of the crop area (36.4, 63.9, 3.0, and 6.0), regardless of depth (30 and 100 cm for C and N). Land use change for pastures in the Arc of Deforestation region of the Amazon maintains SOC and N stocks in the soil and is more sustainable than the agricultural system with black pepper, as long as the conditions of soil, climate, and cultivation are similar. Part of the C3-derived carbon from the forest was replaced by C4-derived C from grasses at soil depths up to 100 cm.
Keywords: 13C isotopic; land use; pasture; ratio C:N